PELESTARIAN BUDAYA LITERASI MASYARAKAT DESA KABUL MELALUI POJOK BACA DAN KEGIATAN PENDIDIKAN PADA ANAK SEKOLAH DASAR - Suwandi, Danu; Prayitno, Reynara Hasan; Mauliddya, Sinta; Gunawan, Muhammad Hendri; Putri, Yeni Septiani; Hoke, Tiza Olivia Virginia; Mahargianti, Rr. Oktaviviana; Agisna, Ulya; Astuti, Maesarah; Ramdani, Nurlaelatul Qadri (Universitas Mataram, 2025)
The main objective of the 2025 Community Service Program (KKN) of Mataram University is to improve the literacy culture of the community in Kabul Village, Praya Barat Daya District, Central Lombok Regency. Low reading interest, lack of learning resources, and lack of understanding of the value of education are some of the problems faced by this village. By creating a Reading Corner and organizing various literacy-based educational events, we hope to increase the enthusiasm of elementary school students in reading. In this study, we used a qualitative descriptive approach that included documentation, interviews, and observation. Surveys, social activities, the establishment of a Reading Corner, and exercises such as reading aloud, book reviews, story writing, and reading-based projects were all part of the program's implementation. The results of these activities show that children have become more interested in reading, more actively participate in the community, and are more aware of the value of literacy. In addition, this initiative has succeeded in encouraging collaboration between students, village leaders, and the community to improve the learning environment.